Is semiquantitative culture of central vein catheter tips useful in the diagnosis of catheter-associated bacteremia? - Collignon, P J (1986)
Semiquantitative culturing of catheter tips has been used as an index of catheter-related bacteremia. As the sensitivity and predictive values of this test have not been determined, we studied 780 tips from central vein catheters inserted into 440 critically ill patients in an intensive care unit. The results were correlated with clinical data for 30 bacteremic episodes which occurred in these patients, 14 of which were catheter related. When five or more colonies per plate were taken as a positive result, the sensitivity of the method was 92%, and the specificity was 83%. Although the predictive value of a negative result was excellent (99.8%), the predictive value of a positive result was low (8.8%) in our patient population, which had a relatively low incidence of catheter-related bacteremia (2%). We conclude that a semiquantitative culture technique is useful in the diagnosis of bacteremia associated with central vein catheters.